2020
DOI: 10.3390/agronomy10040579
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Edible Flower Production: A Case Study

Abstract: Nowadays the heightened awareness of the critical trend in resource depletion impels to improve the eco − sustainability of any productive process. The research presented in this paper aims to quantify the environmental impact of the emerging productive process of edible flowers, focusing on two model species, i.e., Begonia x semperflorens − cultorum hort and Viola cornuta L., and two types of product, i.e., flowering potted plants sold in plastic vases and packaged flowers ready to be consumed. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Edible ornamentals represent fresh or raw vegetal food that can also improve the dish presentation and display [34,35]. Many edible ornamentals are rich in bioactive compounds and can be considered as functional or nutraceutical food [36]. Several studies have reported that phenolic compounds of edible flowers can have potential benefits on human health because these molecules have strong antioxidant activities and are able to scavenge reactive oxygen species (ROS) [37].…”
Section: Indoormentioning
confidence: 99%
“…Edible ornamentals represent fresh or raw vegetal food that can also improve the dish presentation and display [34,35]. Many edible ornamentals are rich in bioactive compounds and can be considered as functional or nutraceutical food [36]. Several studies have reported that phenolic compounds of edible flowers can have potential benefits on human health because these molecules have strong antioxidant activities and are able to scavenge reactive oxygen species (ROS) [37].…”
Section: Indoormentioning
confidence: 99%
“…Today, the assortment of edible flowers includes several species that are used to improve the aesthetic appearance, color, and aroma of foods but also for their nutritional properties [2,[9][10][11][12][13]. Edible flowers contain indeed several bioactive compounds (vitamins, minerals, phenolic substances), while they are poor in fat and proteins [2,3,9,11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Edible flowers can be used raw or fresh, as a garnish or an integral part of a dish. The flowers are consumed both as a conventional food and as a functional or nutraceutical food, thanks to the high and diversified content of bioactive compounds present in the various floral parts depending on the species (Falla et al, 2020 ).…”
Section: Biodiversity Of Edible Flowersmentioning
confidence: 99%